Gastric microbiota: an emerging player in gastric cancer - Zhou, Shizhen; Li, Chenxi; Liu, Lixiang; Yuan, Qinggang; Miao, Ji; Wang, Hao; Ding, Chao; Guan, Wenxian (Frontiers in Microbiology, 2023)
Gastric cancer (GC) is a common cancer worldwide with a high mortality rate. Many microbial factors influence GC, of which the most widely accepted one is Helicobacter pylori (H. pylori) infection. H. pylori could cause inflammation, immune reactions and activation of multiple signaling pathways, leading to acid deficiency, epithelial atrophy, dysplasia and ultimately GC. It has been proved that complex microbial populations exist in the human stomach. H. pylori can affect the abundance and diversity of other bacteria. The interactions among gastric microbiota are collectively implicated in the onset of GC. Certain intervention strategies may regulate gastric homeostasis and mitigate gastric disorders. Probiotics, dietary fiber, and microbiota transplantation can potentially restore healthy microbiota. In this review, we elucidate the specific role of the gastric microbiota in GC and hope these data can facilitate the development of effective prevention and therapeutic approaches for GC.